Neural circuitry underlying effects of context on human pain‐related fear extinction in a renewal paradigm - Icenhour, Adriane (Hum Brain Mapp, 2015)
OBJECTIVES: The role of context in pain‐related extinction learning remains poorly understood. We analyzed the neural mechanisms underlying context‐dependent extinction and renewal in a clinically relevant model of conditioned abdominal pain‐related fear. Experimental design: In this functional magnetic resonance imaging study, two groups of healthy volunteers underwent differential fear conditioning with painful rectal distensions as unconditioned stimuli (US) and visual conditioned stimuli (CS(+); CS(−)). The extinction context was changed in an experimental group (context group), which was subsequently returned into the original learning context to test for renewal. No context changes occurred in the control group. Group differences in CS‐induced differential neural activation were analyzed along with skin conductance responses (SCR), CS valence and CS‐US contingency ratings. Principal observations: During extinction, group differences in differential neural activation were observed in dorsolateral (dlPFC) and ventromedial (vmPFC) prefrontal cortex and amygdala, mainly driven by enhanced activation in response to the CS(−) in the control group. During renewal, observed group differences in activation of dlPFC and orbitofrontal cortex (OFC) resulted primarily from differential modulation of the CS(−) in the absence of group differences in response to CS(+) or SCR. CONCLUSION: The extinction context affects the neural processing of nonpain predictive safety cues, supporting a role of safety learning in pain‐related memory processes. Hum Brain Mapp 36:3179–3193, 2015. © 2015 Wiley Periodicals, Inc.